Cooperative Transcription Factor Induction Mediates Hemogenic Reprogramming - Gomes, Andreia (2018)
During development, hematopoietic stem and progenitor cells (HSPCs) arise from specialized endothelial cells by a process termed endothelial-to-hematopoietic transition (EHT). The genetic program driving human HSPC emergence remains largely unknown. We previously reported that the generation of hemogenic precursor cells from mouse fibroblasts recapitulates developmental hematopoiesis. Here, we demonstrate that human fibroblasts can be reprogrammed into hemogenic cells by the same transcription factors. Induced cells display dynamic EHT transcriptional programs, generate hematopoietic progeny, possess HSPC cell surface phenotype, and repopulate immunodeficient mice for 3 months. Mechanistically, GATA2 and GFI1B interact and co-occupy a cohort of targets. This cooperative binding is reflected by engagement of open enhancers and promoters, initiating silencing of fibroblast genes and activating the hemogenic program. However, GATA2 displays dominant and independent targeting activity during the early phases of reprogramming. These findings shed light on the processes controlling human HSC specification and support generation of reprogrammed HSCs for clinical applications.